HOLISTIC DEVELOPMENT OF PSYCHO DELIVERANCE SPIRITUAL (PSYCHODELSPY) HEALING THERAPY FOR CHRISTIAN CONGREGATIONS USING IMMUNITY SCIENCE VICTIMS OF OCCULTISM - Anry Krismanto Nababan; Rogate Gultom; Arip Surpi Sitompul (ADISAM Publisher, 2026)
The practice of occultism, including invulnerability magic, remains a widespread phenomenon across various segments of society, including among Christians. Belief in supernatural powers and the ability to be immune to physical attacks is often a special attraction, especially for those who feel vulnerable or seek protection beyond the reach of reason. Immunity science, with all its rituals and practices, often involves aspects that contradict religious teachings, especially Christianity. This practice not only has an impact on spiritual aspects, but can also cause psychological and social problems for its adherents.The development of spiritual healing therapies is very rare, but the number of victims of occultism has an increasing tendency, especially among practitioners of invulnerability. This study uses qualitative procedures to describe data to produce or test the developed product, but its main focus is on the creation and validation of a product, not pure data analysis. The research method is oriented towards the development of a product from Psycho Deliverance Spiritual healing therapy and testing its effectiveness. The results of the evaluation of this therapy have produced a new therapy product from the previous one.